Uzbekistan : Agri-Food Job Diagnostic - World Bank (World Bank, Washington, DC, 2020)
Jobs are among the most important economic and social concerns in Uzbekistan. This report takes stock of the job situation in Uzbekistan’s broader agri-food sector and shows pathways for increasing sustainable employment. It lays out a roadmap for operationalization of the implicit job agenda of the recently adopted agricultural strategy for Uzbekistan. The illustrative scenarios presented in the report show that public policies and investments can help the agri-food sector increase employment between 19 and 32 percentage points in 2030 compared to 2019, allowing annual creation of 0.7 to 1.3 million jobs, more than enough to absorb 600,000 young newcomers to Uzbekistan’s labor market (due to demographic reasons). Particularly the horticulture sub-sectors with strong comparative advantages and market opportunities has a potential for more productive and sustainable jobs. Those jobs will be inclusive, being available to women and youth not only in Tashkent and other large cities, but also in rural areas and secondary towns. And, they will be critical to raise people’s incomes and lift them out of poverty, as well as helping the agri-food sector enhance food security and supporting economic growth through its strong spillovers to regional and rural economies.